Petrofacies and diagenetic processes of la Victoria formation (Early Miocene), Dina oil field, upper Magdalena valley basin, Colombia. - Gomez Caro, Juan Jose; Carreño Parra, Angelica María; P´érez Trejos, María del Rosario; Pérez, Edgar Ricardo; Peña Peña, Luis Fernando; Henao, José Antonio; Rios, Carlos; Rueda Acevedo, Luz Helena (CT&F - Ciencia, Tecnología y Futuro, 2020)
The sandstones at the base of the Honda Group (La Victoria Formation - Early Miocene), in the Dina Field, Upper Magdalena Valley Basin (UMVB) – Colombia, which are present in the analyzed interval of the Dina Norte 27 and Dina Norte 37 wells, are composed of immature clastic rocks classified as Litharenites / Feldspathic Litharenites, due to the presence of volcanic fragments, feldspar / plagioclase and unstable minerals. They are texturally immature due to poor selection and low roundness of the detritus. The following sequence of diagenetic processes is proposed: minor compaction; grain coating by illite/smectite detritical clay, dissolution of unstable minerals, zeolite (heulandite) precipitation, partial precipitation of nonferroan calcite cement and finally chloritization of clays prior to hydrocarbon migration.